Low-temperature (330 °C) crystallization and dopant activation of Ge thin films via AgSb-induced layer exchange: Operation of an n-channel polycrystalline Ge thin-film transistor. (24th August 2017) - Suzuki, Tatsuya; Joseph, Benedict Mutunga; Fukai, Misato; Kamiko, Masao; Kyuno, Kentaro
Abstract: Ge thin films have been prepared by layer-exchange metal-induced crystallization using AgSb alloy as a catalyst. Not only the crystallization of Ge, but also the incorporation of Sb atoms into the crystalline Ge layer and their activation have been realized during the process at a temperature as low as 330 °C. Thin-film transistors have been fabricated using the Ge thin films as channel layers and the operation of an n-channel transistor with an on/off ratio of over 300 has been demonstrated.